Quasi-two-dimensional red light perovskite LED device and preparation method thereof
By adopting an interface modification strategy in quasi-two-dimensional red light perovskite LED devices, and using calcium lignin sulfonate to adjust the phase distribution and crystallization quality of perovskite films, the problem of poor photoelectric performance of perovskite LED devices is solved, and higher photoelectric performance and lower production costs are achieved.
Patent Information
- Application Number
- CN202510099953.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-22
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2045-01-22
AI Technical Summary
The photoelectric performance of quasi-two-dimensional red light perovskite LED devices is mainly due to the uneven phase distribution of perovskite films, low energy transmission efficiency, poor crystallization quality and many defects, resulting in increased non-radiative recombination and low luminous performance.
Using the interface modification strategy, by depositing calcium lignin sulfonate molecules between the hole transport layer and the perovskite layer, the phase distribution of the perovskite film is adjusted, the wetting of the perovskite precursor solution and the bottom interface is improved, and the crystallization quality and coverage of the film are improved.
It effectively suppresses the formation of small n phases, promotes the generation of large n phases, optimizes the phase distribution of perovskites, improves energy transfer ability, reduces the density of film defect states, and improves the photoelectric performance of the device, including reducing the turn-on voltage, improving brightness and external quantum efficiency.
Smart Images

Figure CN119923170A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of light emitting diodes, and in particular to a quasi-two-dimensional red light perovskite LED device and a preparation method thereof. Background Art
[0002] The unique properties of perovskite materials between inorganic semiconductors and organic materials give them excellent optoelectronic properties, especially in the preparation of high-efficiency light-emitting diodes (LEDs). In recent years, with the continuous deepening of related research, the attention to quasi-two-dimensional perovskites with high fluorescence quantum efficiency and narrow half-width has gradually increased. Due to their high photoluminescence quantum yield, adjustable optical band gap, excellent color purity and low-cost solution processability, they have broad prospects in the fields of light-emitting diodes and display applications. Quasi-two-dimensional perovskite LEDs are in the initial development stage and still face many difficulties and challenges. However, the optoelectronic properties of light-emitting diodes using perovskite materials as the light-emitting layer are still far lower than those of the most advanced organic light-emitting diodes. This is mainly due to the uneven phase distribution of perovskite films, resulting in too low energy transfer efficiency, and insufficient wettability between the solution and the bottom interface, resulting in poor film crystallization quality. The effects of these two factors will lead to poor optoelectronic performance of perovskite LED devices.
[0003] Quasi-two-dimensional red perovskite is generally obtained by adding excess organic cations to iodine-based three-dimensional perovskite. During the growth process, by adjusting the content of organic cations in the precursor, the quasi-two-dimensional red perovskite will generate a layered perovskite phase containing different numbers of lead halide octahedron layers. Among these quasi-two-dimensional perovskite phases, the n phase is a quasi-two-dimensional perovskite phase with n layers of lead halide octahedrons. The small n phase is usually referred to as the n = 1 and 2 phases, the large n phase is the n = 3 and 4 phases, and the luminescent phase is the phase with the largest n value in the large n phase. The small n phase in the quasi-two-dimensional perovskite has a large number of defects, which will lead to serious non-radiative recombination. At the same time, its wide band gap will also hinder the injection and transmission of carriers, and the excessive content of the small n phase will lead to incomplete energy transfer during the energy transfer process, resulting in low luminescence performance. However, during the growth and nucleation process of the quasi-two-dimensional perovskite, the high formation energy of the small n phase makes it easier to form and has a higher content, while the content of the large n phase is less, so the distribution of the quasi-two-dimensional red perovskite phase is not conducive to luminescence. Effectively managing the distribution of quasi-two-dimensional red light perovskite phase, that is, inhibiting the generation of small n phase and promoting its transformation into large n phase, is one of the effective means to improve the performance of quasi-two-dimensional red light perovskite LEDs. In addition, for the bottom-emitting upright LED device structure composed of an anode, a hole transport layer, a light-emitting layer, an electron transport layer, and a cathode, the film-forming quality of the light-emitting layer, i.e., the perovskite film, is mainly affected by the material of the upper transport layer. Currently, commonly used transport layer materials are mainly organic polymers with certain carrier mobility, such as PMMA (polymethyl methacrylate), PVK (poly(9-vinylcarbazole)), TFB (poly[(9,9-dioctylfluorenyl-2,7-diyl)-alt-(4,4'-(N-(4-n-butyl)phenyl)-diphenylamine)]), PTAA (poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine]), and POLY-TPD (poly[bis(4-phenyl)(4-butylphenyl)amine]). However, their strong hydrophobicity often leads to poor crystallization quality of the perovskite film spin-coated thereon, which in turn leads to more defects and non-radiative recombination, destroying the photoelectric performance of the perovskite LED device.
[0004] There are many reasons that limit the optoelectronic performance of quasi-two-dimensional red perovskite light-emitting diodes. Unreasonable phase distribution and poor film quality are two of the more important factors. First, in quasi-two-dimensional perovskites, the small n phase (n≤2) has a low formation energy and is therefore easy to form in large quantities. However, the small n phase with strong electron-phonon coupling is mainly non-radiative recombination, which is not conducive to luminescence. In addition, the excessive small n phase makes it difficult for excitons to match the large n phase nearby, thereby hindering the energy transfer process. When the energy transfer from the small n phase to the large n phase is insufficient, the performance of the device, especially the EQE (external quantum efficiency), is often low. Secondly, the film quality of the perovskite film with an upright device structure is mainly affected by the material of the upper transport layer. Currently, the commonly used transport layer materials are mainly organic polymers, but their strong hydrophobicity often leads to poor crystallization quality of the perovskite film, which in turn leads to more defects and non-radiative recombination.
[0005] Therefore, how to optimize the phase distribution of quasi-two-dimensional perovskite films and improve the film quality is of great significance for the preparation of high-performance perovskite optoelectronic devices. In the prior art, doping or additives are generally used to adjust the phase distribution, which will have a great impact on the quantum confinement effect of quasi-two-dimensional perovskite, resulting in serious emission deviation. Summary of the invention
[0006] The object of the present invention is to provide a method for preparing a quasi-two-dimensional red light perovskite LED device to solve the problems raised in the above background technology.
[0007] To achieve the above objectives, the embodiments of the present invention provide the following technical solutions:
[0008] A method for preparing a quasi-two-dimensional red light perovskite LED device comprises the following steps:
[0009] The PEDOT:PSS aqueous solution is deposited onto the surface of the substrate etched with the anode electrode by spin coating, and the first annealing treatment is performed;
[0010] TFB and PVK are mixed and dissolved in a chlorobenzene solution, and are deposited on the surface of the substrate after the first step annealing treatment by spin coating, and then a second step annealing treatment is performed;
[0011] Depositing the calcium lignin sulfonate solution onto the surface of the substrate after the second step annealing treatment by spin coating;
[0012] Dissolving lead iodide, cesium iodide, zinc iodide, 3,3-diphenylpropylamine iodide, 1-naphthylamine iodide and phenylethylamine iodide in an N,N-dimethylformamide solution to obtain a perovskite precursor solution;
[0013] The perovskite precursor solution is dropped onto the surface of the substrate treated in the above step, a thin film is prepared by spin coating, and the thin film is subjected to a third step annealing treatment;
[0014] An electron transport layer and a cathode electrode are evaporated on the above film to obtain the quasi-two-dimensional red light perovskite LED device.
[0015] Preferably, the anode electrode is indium tin oxide, and the substrate is glass sputtered with indium tin oxide.
[0016] Preferably, the temperature of the first annealing treatment is 145-155°C; the temperature of the second annealing treatment is 155-165°C; and the temperature of the third annealing treatment is 65-75°C.
[0017] Preferably, the concentration of the PEDOT:PSS aqueous solution is 1.3-1.7 wt %.
[0018] Preferably, the mass ratio of TFB to PVK is 1:(4-6).
[0019] Preferably, the calcium lignin sulfonate solution is an aqueous solution of calcium lignin sulfonate, and the concentration thereof is 8-12 mg / mL.
[0020] Preferably, the molar ratio of lead iodide, cesium iodide, zinc iodide, 3,3-diphenylpropylamine iodide, 1-naphthylamine iodide and phenethylamine iodine is (8-10):(4-6):(0.5-1.5):(0.5-1.5):(3-5):(4-6).
[0021] Preferably, the evaporated electron transport layer is 2,4,6-tris[3-(diphenylphosphinoyl)phenyl]-1,3,5-triazole.
[0022] Preferably, the cathode electrode is lithium fluoride and aluminum.
[0023] Another object of the present invention is to provide a quasi-two-dimensional red light perovskite LED device prepared by the above preparation method.
[0024] The preparation method of the quasi-two-dimensional red light perovskite LED device provided by the present invention can achieve a very good phase regulation effect by using an interface modification strategy. While adjusting the phase distribution and enhancing the energy transfer ability of the quasi-two-dimensional perovskite, under the action of the highly hydrophilic sulfonate group, the wettability of the perovskite precursor solution and the bottom interface is improved, and the crystallization quality and film coverage of the perovskite film are improved. Under the dual-functional action of the interface modification strategy, the film defect state density is reduced, the non-radiative recombination is reduced, and the energy funnel effect of the quasi-two-dimensional perovskite is promoted, thereby improving the photoelectric performance of the device.
[0025] The preparation method of the quasi-two-dimensional red light perovskite LED device provided by the present invention is simple to operate, less time consuming, highly efficient and extremely low in cost; the calcium lignin sulfonate deposition layer used as interface modification in the present invention can significantly adjust the phase distribution of the quasi-two-dimensional perovskite, enhance the photoelectric performance of the device and improve the quality of the energy-level film; the quasi-two-dimensional red light perovskite LED device prepared by the present invention has a low turn-on voltage, high brightness and high external quantum efficiency (EQE).
[0026] In addition, the calcium lignin sulfonate used in the present invention is a cheap, pollution-free green material with extremely low production cost. Its main raw material, lignin, is the second largest biomass resource after cellulose in terms of reserves, and is also the only renewable aromatic compound resource in nature. The extremely low raw material and production costs are extremely beneficial for replacing expensive additives, being applied in the field of perovskite research, and even realizing industrialization. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 The external quantum efficiency-current density characteristic curves of the LED devices prepared in Example 1 and Comparative Example 1 are shown.
[0028] Figure 2 The current density-voltage-brightness characteristic curves of the LED devices prepared in Example 1 and Comparative Example 1 are shown.
[0029] Figure 3 The electroluminescence spectra of the LED devices prepared in Example 1 and Comparative Example 1 are shown.
[0030] Figure 4 The absorption spectra of the LED devices prepared in Example 1 and Comparative Example 1 are shown in FIG.
[0031] Figure 5 The photoluminescence spectra of the LED devices prepared in Example 1 and Comparative Example 1 are shown.
[0032] Figure 6 This is a comparison chart of the water contact angle test of the LED devices prepared in Example 1 and Comparative Example 1.
[0033] Figure 7 Atomic force microscope images (AFM) of the LED devices prepared in Example 1 and Comparative Example 1. DETAILED DESCRIPTION
[0034] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0035] With respect to the technical problems raised by the background technology, the embodiment of the present invention adopts an interface modification strategy, that is, a layer of calcium lignin sulfonate molecules is introduced between the hole transport layer and the perovskite layer to manage the phase distribution of the perovskite film. The sulfonate groups in the substance are combined with the organic long chains in the perovskite solution to inhibit the formation and accumulation of the small n phase (i.e., n=2); specifically, the calcium lignin sulfonate molecules deposited between the hole transport layer and the perovskite layer can diffuse with the organic cations (3,3-diphenylpropylamine cations and 1-naphthylamine cations) in the bottom interface perovskite precursor. The sulfonate group in the deposited calcium lignin sulfonate molecules has a strong hydrophilicity, which can greatly improve the wettability of the perovskite precursor solution and the bottom interface, improve the crystallization quality of the perovskite film, reduce the roughness, reduce the defect state density and thus inhibit non-radiative recombination, thereby improving the performance of the quasi-two-dimensional red light perovskite LED device.
[0036] Example 1: This example provides a method for preparing a quasi-two-dimensional red light perovskite LED device with calcium lignin sulfonate as interface modification, which comprises the following steps:
[0037] S1, a conductive glass substrate etched with an anode electrode ITO (indium tin oxide) is repeatedly cleaned with deionized water, ethanol and dichloromethane, and then cleaned with a UV ozone machine for 15 minutes;
[0038] S2, depositing a 1.5 wt % poly(3,4-ethylenedioxythiophene)-polystyrene sulfonic acid (PEDOT:PSS) aqueous solution onto the surface of the substrate treated in step S1 by spin coating, and performing a first annealing treatment at a temperature of 150° C. for 20 minutes;
[0039] S3, 0.5 mg of poly [(9,9-di-n-octylfluorenyl-2,7-diyl)-alt-(4,4'-(N-(4-n-butyl)phenyl)-diphenylamine)] (TFB) and 2.5 mg of poly (9-vinylcarbazole) (PVK) were mixed and dissolved in 1 mL of chlorobenzene solution, and deposited on the surface of the substrate treated in the above step S2 by spin coating, and a second step annealing treatment was performed at a temperature of 160° C. for 20 minutes;
[0040] S4, dissolving 10 mg of calcium lignin sulfonate in 1 mL of deionized water to obtain a calcium lignin sulfonate solution; and then depositing the calcium lignin sulfonate solution onto the surface of the substrate treated in step S3 by spin coating;
[0041] S5, dissolving 0.09 mmol of lead iodide, 0.05 mmol of cesium iodide, 0.01 mmol of zinc iodide, 0.01 mmol of 3,3-diphenylpropylamine iodide, 0.04 mmol of 1-naphthylamine iodide and 0.05 mmol of phenylethylamine iodide in 1 mL of N,N-dimethylformamide solution to obtain a perovskite precursor solution;
[0042] S6, dropping the perovskite precursor solution onto the surface of the substrate treated in step S4, and preparing a thin film by spin coating, and then placing the thin film on a heating table and heating it to 70° C. for a third annealing treatment for 10 minutes;
[0043] S7. Place the above film into an evaporator, evaporate a 2,4,6-tris[3-(diphenylphosphinoyl)phenyl]-1,3,5-triazole (PO-T2T) electron transport layer (35 nm thick) and a cathode electrode (composed of lithium fluoride and aluminum, with thicknesses of 1 nm and 100 nm, respectively) to obtain a quasi-two-dimensional red light perovskite LED device.
[0044] Embodiment 2: This embodiment provides a method for preparing a quasi-two-dimensional red light perovskite LED device, which comprises the following steps:
[0045] S1. The conductive glass substrate etched with the anode electrode ITO is repeatedly cleaned with deionized water, ethanol and dichloromethane, and then cleaned with a UV ozone machine for 15 minutes;
[0046] S2, depositing a 1.3 wt % PEDOT:PSS aqueous solution onto the substrate surface treated in step S1 by spin coating, and performing a first annealing treatment at 145° C. for 20 minutes;
[0047] S3, 0.5 mg of TFB and 2 mg of PVK were mixed and dissolved in 1 mL of chlorobenzene solution, and deposited on the surface of the substrate treated in step S2 by spin coating, and a second annealing treatment was performed at a temperature of 155° C. for 20 minutes;
[0048] S4, dissolving 8 mg of calcium lignin sulfonate in 1 mL of deionized water to obtain a calcium lignin sulfonate solution; and then depositing the calcium lignin sulfonate solution onto the surface of the substrate treated in step S3 by spin coating;
[0049] S5, dissolving 0.08 mmol of lead iodide, 0.04 mmol of cesium iodide, 0.005 mmol of zinc iodide, 0.005 mmol of 3,3-diphenylpropylamine iodide, 0.03 mmol of 1-naphthylamine iodide and 0.04 mmol of phenylethylamine iodide in 1 mL of N,N-dimethylformamide solution to obtain a perovskite precursor solution;
[0050] S6, dropping the above perovskite precursor solution onto the surface of the substrate treated in step S4, and preparing a thin film by spin coating, and then placing the above film on a heating table and heating it to 65° C. for a third annealing treatment for 10 minutes;
[0051] S7. Place the above film into an evaporator, evaporate a PO-T2T electron transport layer (35 nm thick) and a cathode electrode (composed of lithium fluoride and aluminum, with thicknesses of 1 nm and 100 nm respectively) to obtain a quasi-two-dimensional red light perovskite LED device.
[0052] Embodiment 3: This embodiment provides a method for preparing a quasi-two-dimensional red light perovskite LED device, which comprises the following steps:
[0053] S1. The conductive glass substrate etched with the anode electrode ITO is repeatedly cleaned with deionized water, ethanol and dichloromethane, and then cleaned with a UV ozone machine for 15 minutes;
[0054] S2, depositing a 1.7 wt % PEDOT:PSS aqueous solution onto the surface of the substrate treated in step S1 by spin coating, and performing a first annealing treatment at a temperature of 155° C. for 20 minutes;
[0055] S3, 0.5 mg of TFB and 3 mg of PVK were mixed and dissolved in 1 mL of chlorobenzene solution, and deposited on the surface of the substrate treated in step S2 by spin coating, and a second annealing treatment was performed at 165° C. for 20 minutes;
[0056] S4, dissolving 12 mg of calcium lignin sulfonate in 1 mL of deionized water to obtain a calcium lignin sulfonate solution; and then depositing the calcium lignin sulfonate solution onto the surface of the substrate treated in step S3 by spin coating;
[0057] S5, dissolving 0.1 mmol of lead iodide, 0.06 mmol of cesium iodide, 0.015 mmol of zinc iodide, 0.015 mmol of 3,3-diphenylpropylamine iodide, 0.05 mmol of 1-naphthylamine iodide and 0.06 mmol of phenylethylamine iodide in 1 mL of N,N-dimethylformamide solution to obtain a perovskite precursor solution;
[0058] S6, dropping the above perovskite precursor solution onto the surface of the substrate treated in step S4, and preparing a thin film by spin coating, and then placing the above film on a heating table and heating it to 75° C. for a third annealing treatment for 10 minutes;
[0059] S7. Place the above film into an evaporator, evaporate a PO-T2T electron transport layer (35 nm thick) and a cathode electrode (composed of lithium fluoride and aluminum, with thicknesses of 1 nm and 100 nm respectively) to obtain a quasi-two-dimensional red light perovskite LED device.
[0060] Embodiment 4: This embodiment provides a method for preparing a quasi-two-dimensional red light perovskite LED device, which comprises the following steps:
[0061] S1. The conductive glass substrate etched with the anode electrode ITO is repeatedly cleaned with deionized water, ethanol and dichloromethane, and then cleaned with a UV ozone machine for 15 minutes;
[0062] S2, depositing a 1.4 wt % PEDOT:PSS aqueous solution onto the substrate surface treated in step S1 by spin coating, and performing a first annealing treatment at 148° C. for 20 minutes;
[0063] S3, 0.5 mg of TFB and 2.6 mg of PVK were mixed and dissolved in 1 mL of chlorobenzene solution, and deposited on the surface of the substrate treated in step S2 by spin coating, and a second annealing treatment was performed at 158° C. for 20 minutes;
[0064] S4, dissolving 9 mg of calcium lignin sulfonate in 1 mL of deionized water to obtain a calcium lignin sulfonate solution; and then depositing the calcium lignin sulfonate solution onto the surface of the substrate treated in step S3 by spin coating;
[0065] S5, dissolving 0.09 mmol of lead iodide, 0.04 mmol of cesium iodide, 0.012 mmol of zinc iodide, 0.008 mmol of 3,3-diphenylpropylamine iodide, 0.05 mmol of 1-naphthylamine iodide and 0.04 mmol of phenylethylamine iodide in 1 mL of N,N-dimethylformamide solution to obtain a perovskite precursor solution;
[0066] S6, dropping the above perovskite precursor solution onto the surface of the substrate treated in step S4, and preparing a thin film by spin coating, and then placing the above film on a heating table and heating it to 68° C. for a third annealing treatment for 10 minutes;
[0067] S7. Place the above film into an evaporator, evaporate a PO-T2T electron transport layer (35 nm thick) and a cathode electrode (composed of lithium fluoride and aluminum, with thicknesses of 1 nm and 100 nm respectively) to obtain a quasi-two-dimensional red light perovskite LED device.
[0068] Embodiment 5: This embodiment provides a method for preparing a quasi-two-dimensional red light perovskite LED device, which comprises the following steps:
[0069] S1. The conductive glass substrate etched with the anode electrode ITO is repeatedly cleaned with deionized water, ethanol and dichloromethane, and then cleaned with a UV ozone machine for 15 minutes;
[0070] S2, depositing a 1.6 wt % PEDOT:PSS aqueous solution onto the substrate surface treated in step S1 by spin coating, and performing a first annealing treatment at 152° C. for 20 minutes;
[0071] S3, 0.5 mg of TFB and 2.8 mg of PVK were mixed and dissolved in 1 mL of chlorobenzene solution, and deposited on the surface of the substrate treated in step S2 by spin coating, and a second annealing treatment was performed at 162° C. for 20 minutes;
[0072] S4, dissolving 11 mg of calcium lignin sulfonate in 1 mL of deionized water to obtain a calcium lignin sulfonate solution; and then depositing the calcium lignin sulfonate solution onto the surface of the substrate treated in step S3 by spin coating;
[0073] S5, dissolving 0.09 mmol of lead iodide, 0.06 mmol of cesium iodide, 0.01 mmol of zinc iodide, 0.01 mmol of 3,3-diphenylpropylamine iodide, 0.05 mmol of 1-naphthylamine iodide and 0.04 mmol of phenylethylamine iodide in 1 mL of N,N-dimethylformamide solution to obtain a perovskite precursor solution;
[0074] S6, dropping the above perovskite precursor solution onto the surface of the substrate treated in step S4, and preparing a thin film by spin coating, and then placing the above film on a heating table and heating it to 72° C. for a third annealing treatment for 10 minutes;
[0075] S7. Place the above film into an evaporator, evaporate a PO-T2T electron transport layer (35 nm thick) and a cathode electrode (composed of lithium fluoride and aluminum, with thicknesses of 1 nm and 100 nm respectively) to obtain a quasi-two-dimensional red light perovskite LED device.
[0076] Comparative Example 1: This comparative example provides a method for preparing a quasi-two-dimensional red light perovskite LED device without calcium lignin sulfonate as interface modification, which comprises the following steps:
[0077] S1, a conductive glass substrate etched with an anode electrode ITO (indium tin oxide) is repeatedly cleaned with deionized water, ethanol and dichloromethane, and then cleaned with a UV ozone machine for 15 minutes;
[0078] S2, depositing a 1.5 wt % poly(3,4-ethylenedioxythiophene)-polystyrene sulfonic acid (PEDOT:PSS) aqueous solution onto the surface of the substrate treated in step S1 by spin coating, and performing a first annealing treatment at a temperature of 150° C. for 20 minutes;
[0079] S3, 0.5 mg of poly [(9,9-di-n-octylfluorenyl-2,7-diyl)-alt-(4,4'-(N-(4-n-butyl)phenyl)-diphenylamine)] (TFB) and 2.5 mg of poly (9-vinylcarbazole) (PVK) were mixed and dissolved in 1 mL of chlorobenzene solution, and deposited on the surface of the substrate treated in the above step S2 by spin coating, and a second step annealing treatment was performed at a temperature of 160° C. for 20 minutes;
[0080] S4, dissolving 0.09 mmol of lead iodide, 0.05 mmol of cesium iodide, 0.01 mmol of zinc iodide, 0.01 mmol of 3,3-diphenylpropylamine iodide, 0.04 mmol of 1-naphthylamine iodide and 0.05 mmol of phenylethylamine iodide in 1 mL of N,N-dimethylformamide solution to obtain a perovskite precursor solution;
[0081] S5, dropping the above perovskite precursor solution onto the surface of the substrate treated in step S3, and preparing a thin film by spin coating, and then placing the above film on a heating table and heating it to 70° C. for a third annealing treatment for 10 minutes;
[0082] S6. Place the above film into an evaporator, evaporate a 2,4,6-tris[3-(diphenylphosphinoyl)phenyl]-1,3,5-triazole (PO-T2T) electron transport layer (35 nm thick) and a cathode electrode (composed of lithium fluoride and aluminum, with thicknesses of 1 nm and 100 nm, respectively) to obtain a quasi-two-dimensional red light perovskite LED device.
[0083] Performance test: The LED device without calcium lignin sulfonate as interface modification prepared in Comparative Example 1 (marked as "Control" in the accompanying drawings) and the LED device with calcium lignin sulfonate as interface modification prepared in Example 1 (marked as "Target" in the accompanying drawings) were compared in various performances. The results are as follows: Figure 1-Figure 7 Specifically, Figure 1 As shown in the figure, it is found that the interface-modified LED device (luminous area 1 cm 2 ), its core performance indicator, external quantum efficiency (EQE), has been significantly improved; Figure 2 As shown, the modified LED device prepared in Example 1 has a lower current density at the same voltage, and the luminous brightness increases more with the increase of voltage, indicating that its photoelectric performance is significantly improved; Figure 3As shown in FIG. 1 , after modification, under the same voltage, the EL of the LED device prepared in Example 1 is significantly stronger; Figure 4 As shown in the figure, the absorption peak of the modified perovskite film representing the small n phase decreases, while the absorption peak of the large n phase becomes stronger, indicating that calcium lignin sulfonate can effectively inhibit the growth of the small n phase and promote the formation of the large n phase; Figure 5 As shown in the figure, the emission of the small n phase is reduced after modification, and the emission peak is slightly red-shifted (caused by the large n phase), which is consistent with Figure 4 The phenomena proved are consistent; Figure 6 As shown in Figure 2, the water contact angle of the modified interface is significantly reduced, indicating that calcium lignin sulfonate can effectively improve the wettability of the interface; Figure 7 As shown, the roughness of the modified perovskite film is significantly reduced, indicating that it can effectively improve the quality of the perovskite film.
[0084] In summary, the embodiment of the present invention adopts an interface modification strategy, and deposits calcium lignin sulfonate under the light-emitting layer by spin coating, which will form a uniform wet film. By diffusion, the deposited material in the wet film state diffuses into the quasi-two-dimensional perovskite of the light-emitting layer, affecting its crystallization growth process, thereby regulating the phase distribution of the quasi-two-dimensional perovskite film and avoiding serious luminescence peak shift. In addition, the interface modification strategy can not only achieve phase distribution regulation, but also improve the wettability between the perovskite layer and the bottom interface to improve the crystallization quality of the film, which is impossible to achieve by doping or additive methods. The present invention uses an interface modification strategy with simple process steps to achieve a dual-functional optimization effect that kills two birds with one stone.
[0085] Based on the above-mentioned ideal embodiments of the present invention, the relevant staff can make various changes and modifications without departing from the technical concept of the present invention through the above-mentioned description. The technical scope of the present invention is not limited to the contents of the specification.
Claims
1. A method for preparing a quasi-two-dimensional red light perovskite LED device, characterized in that: The following steps are involved: The PEDOT:PSS aqueous solution is deposited onto the surface of the substrate etched with the anode electrode by spin coating, and the first step of annealing is performed; TFB and PVK are mixed and dissolved in a chlorobenzene solution, and are deposited on the surface of the substrate after the first step annealing treatment by spin coating, and then a second step annealing treatment is performed; Depositing the calcium lignin sulfonate solution onto the surface of the substrate after the second step annealing treatment by spin coating; Dissolving lead iodide, cesium iodide, zinc iodide, 3,3-diphenylpropylamine iodide, 1-naphthylamine iodide and phenylethylamine iodide into an N,N-dimethylformamide solution to obtain a perovskite precursor solution; The perovskite precursor solution is dropped onto the surface of the substrate treated in the above step, a thin film is prepared by spin coating, and the thin film is subjected to a third step annealing treatment; An electron transport layer and a cathode electrode are evaporated on the above film to obtain the quasi-two-dimensional red light perovskite LED device.
2. The method for preparing a quasi-two-dimensional red light perovskite LED device according to claim 1, characterized in that: The anode electrode is indium tin oxide, and the substrate is glass sputtered with indium tin oxide.
3. The method for preparing a quasi-two-dimensional red light perovskite LED device according to claim 1, characterized in that: The temperature of the first annealing treatment is 145-155°C; the temperature of the second annealing treatment is 155-165°C; and the temperature of the third annealing treatment is 65-75°C.
4. The method for preparing a quasi-two-dimensional red light perovskite LED device according to claim 1, characterized in that: The concentration of the PEDOT:PSS aqueous solution is 1.3-1.7 wt %.
5. The method for preparing a quasi-two-dimensional red light perovskite LED device according to claim 1, characterized in that: The mass ratio of TFB and PVK is 1:(4-6).
6. The method for preparing a quasi-two-dimensional red light perovskite LED device according to claim 1, characterized in that: The calcium lignin sulfonate solution is an aqueous solution of calcium lignin sulfonate, and its concentration is 8-12 mg / mL.
7. The method for preparing a quasi-two-dimensional red light perovskite LED device according to claim 1, characterized in that: The molar ratio of lead iodide, cesium iodide, zinc iodide, 3,3-diphenylpropylamine iodide, 1-naphthylamine iodide and phenethylamine iodide is (8-10):(4-6):(0.5-1.5):(0.5-1.5):(3-5):(4-6).
8. The method for preparing a quasi-two-dimensional red light perovskite LED device according to claim 1, characterized in that: The evaporated electron transport layer is 2,4,6-tris[3-(diphenylphosphinoyl)phenyl]-1,3,5-triazole.
9. The method for preparing a quasi-two-dimensional red light perovskite LED device according to claim 1, characterized in that: The cathode electrode is lithium fluoride and aluminum.
10. A quasi-two-dimensional red light perovskite LED device prepared by the preparation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
High power LED radiating ceramic substrate containing perovskite and prepared by low temperature sintering
CN106220184A
Organic-inorganic composite contaminated water purifying filter material and preparation method and application thereof
CN108607529A
Preparation method of low-defect quasi-two-dimensional perovskite film based on methanesulfonic acid negative ion induction
CN110305660A
High-efficiency perovskite solar cell and preparation method thereof
CN111640870A